Respuesta :
[tex]Given equation: \frac{ x^2 - x - 6}{x^2}=\frac{x-6}{2x} +\frac{2x+12}{x}[/tex]
Please see, we have x^2, 2x and x in denominators(bottom) of fractions.
So, LCD of x^2, 2x and x would be 2x^2.
Therefore, we need to multiply given equation by LCD. We get
[tex](2x^2)(\frac{ x^2 - x - 6}{x^2})=2x^2(\frac{x-6}{2x}) +2x^2(\frac{2x+12}{x})[/tex]
On simplifying this step, we get :
[tex]2( x^2 - x - 6)=x(x-6)+2x(12x+2)[/tex]
Therefore, after multiplying each side of the equation by the LCD 2x^2 and simplifying, the resulting equation is
[tex]2( x^2 - x - 6)=x(x-6)+2x(12x+2)[/tex].
Answer:
C) 3x^2 + 20x + 12 = 0
Step-by-step explanation: Because it is the right answer